Casting a new light on the democratic spectator. Issue 7 (3rd October 2022) - Felicetti, Andrea
ABSTRACT: The idea of citizens being mere spectators who "watch" politics is widespread in public and academic debates. Scholarship in relation to democratic theory tends to see spectatorship as a state in which citizens are politically uninterested, isolated, and passive. Although this understanding aptly captures the problems about the idea of spectatorship, it is only a partial awareness and prevents us from seeing that positive forms of spectatorship are also possible. I show that positive spectatorship occurs when citizens show an interest in one or more political problems and, together with others, strive to understand them better. I consider the distinctive elements of this form of spectatorship characterized by careful observance, relationality, and proactivity. I argue that it is normatively desirable, and I reflect on the ways in which positive spectatorship helps thinking about democratizing politics. Relatedly, I also revisit the theatrical metaphor of politics, which is often associated to the concept of spectatorship as something negative for democracy. I argue that, when combined with a proper understanding of spectatorship, the theatrical metaphor can be used originally to envisage ways forward in the democratization of our societies.